2011
DOI: 10.5009/gnl.2011.5.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Features of Hepatitis A between HBsAg-Positive and HBsAg-Negative Patients

Abstract: Background/AimsThe notion that acute hepatitis A superimposed on chronic hepatitis B infection leads to a worse outcome than acute hepatitis A alone remains controversial. The aim of this study was to determine the influence of the presence of hepatitis B surface antigen (HBsAg) on the severity of acute hepatitis A.MethodsWe retrospectively analyzed 449 patients hospitalized for acute hepatitis A from January 2000 to February 2010 and compared clinical outcomes based on the presence of HBsAg.ResultsOf the 449 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…The seroprevalence of HAV infection in patients with chronic liver diseases is similar to that in general population by age ( 30 , 31 ). It has been reported that the clinical features of hepatitis A are severe in patients with chronic HBV infection ( 32 , 33 ). However, the clinical impact of chronic hepatitis B on the prognosis of hepatitis A is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seroprevalence of HAV infection in patients with chronic liver diseases is similar to that in general population by age ( 30 , 31 ). It has been reported that the clinical features of hepatitis A are severe in patients with chronic HBV infection ( 32 , 33 ). However, the clinical impact of chronic hepatitis B on the prognosis of hepatitis A is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical impact of chronic hepatitis B on the prognosis of hepatitis A is still controversial. Kim et al ( 33 ) reported that acute hepatitis A superimposed on chronic HBV infection is associated with serious morbidity and mortality including acute liver failure compared with acute hepatitis alone. Our data revealed that the prevalence of HBsAg in the study population was 3.7%, which is a similar rate in young Korean adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies were limited due to small sample sizes. In contrast, some other reports indicated that patients with acute hepatitis A on chronic hepatitis B had higher peak laboratory abnormalities and more severe outcomes than patients with acute hepatitis A alone, including higher fatality rates (ranging from 6‐ to 59‐fold higher) and fulminant hepatitis (ranging from 7‐ to 22‐fold higher) [Hadler, 1991; Yao, 1991; Kim et al, 2010; Kim et al, 2011]. However, some of these results were calculated from an assumed data not based on the actual investigation [Hadler, 1991; Yao, 1991], or some were conducted in tertiary hospitals, to which more severe patients are referred for liver transplantation or intensive care [Kim et al, 2010, 2011].…”
Section: Discussionmentioning
confidence: 97%
“…As increasing age is associated with an increasing risk for severe acute hepatitis A with complications, stratified analysis for this kind of confounding factor should be needed. In two recent large series reported that HAV‐associated acute liver failure occurred more frequently in HBsAg‐positive patients than in HBsAg‐negative patients as much as 9–22 folds, the age of HBsAg‐positive patients was higher than HBsAg‐negative patients [Kim et al, 2010, 2011]. Finally, this study addressed the underlying chronic hepatitis B state of patients with acute hepatitis A on chronic hepatitis B, which has been not described in most of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…During the methodological quality assessment, potential for bias was assigned to eleven case-control studies (Appendix 2). In Chironna et al (2012), Ciccozzi et al (2002), Hellara et al (2014), Mele et al (1997), Kim et al (2011) and Tosti et al (2008), the "controls/non-ill people" were affected by hepatitis B or C, while in Delarocque-Astagneau et al (2012) and Masia et al (2004), the controls were hepatitis E positive. In Gammie and Wyn-Jones (1997), the odds of acquiring hepatitis A from "being a surfer" was compared against "being a windsurfer", instead of "not being a surfer".…”
Section: Descriptive Statisticsmentioning
confidence: 99%